2019
DOI: 10.1111/imb.12606
|View full text |Cite
|
Sign up to set email alerts
|

miR‐2703 regulates the chitin biosynthesis pathway by targeting chitin synthase 1a in Nilaparvata lugens

Abstract: The chitin biosynthesis pathway is an important physiology process in arthropods. However, few microRNAs (miRNAs) involved in the regulation of the chitin biosynthesis pathway in insects have been reported until now. In this study, four groups of samples that either upregulated or downregulated the chitin biosynthesis pathway were collected for deep sequencing, and a total of 15 unique mature miRNAs with significantly different expression levels were found, including 11 known miRNAs and four novel miRNAs. Subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…49 In other research on N. lugens, miR-2703 was shown to directly regulate chitin synthase 1a, consequently decreasing the survival rate of nymphs with molting defect phenotypes. 51 Overall, these findings indicate that miRNA pathway core genes participate in the regulation of molting during development and in the reproduction of L. serricorne by influencing the expression of miRNAs.…”
Section: Discussionmentioning
confidence: 78%
“…49 In other research on N. lugens, miR-2703 was shown to directly regulate chitin synthase 1a, consequently decreasing the survival rate of nymphs with molting defect phenotypes. 51 Overall, these findings indicate that miRNA pathway core genes participate in the regulation of molting during development and in the reproduction of L. serricorne by influencing the expression of miRNAs.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have attempted to inhibit chitin synthesis in insects mainly by interrupting chitin synthase using RNA interference (RNAi) technology [ 63 66 ]. Some studies have shown that miRNAs are involved in chitin biosynthesis and regulate gene expression during the molting of insects [ 67 70 ]. The present study revealed roles of ncRNAs in chitin metabolism, providing more molecular targets for regulating chitin-related biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA inhibitors, such as mimic (agomir) or inhibitor (antagomir), can be introduced into insects through feeding, injection, or drip infusion, offering novel approaches for pest control [ 23 , 24 , 25 ]. For instance, miR-2703 targets CHS1a for chitin synthesis regulation in response to the 20E signaling pathway in brown planthopper, with the injecting miR-2703 mimic reducing the chitin synthesis, increasing mortality, and causing molting defects [ 26 ]. Similarly, miR-184 regulates the transcription level of CYP303A1 during the molting process in locusts, leading to molting abnormalities and death [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…To comprehensively assess the effects of miR-306 agomir on the population dynamics of S. avenae , we employed the nanomaterial SPc/adjuvant carrier to precisely deliver miR-306 agomir and interfere to newly hatched nymphs within 24 h. Using the two-sex life table method, which has provided valuable insights into the population ecology of target species, serving as essential tools for assessing population fitness and dynamics [ 25 , 26 , 27 , 28 , 29 ], we investigated the impact of miR-306 agomir on the growth, development, and reproductive capability of S. avenae . This research aims to contribute to the development of miRNA-based nucleic acid pesticides and provide new molecular targets and methodologies for effective aphid control.…”
Section: Introductionmentioning
confidence: 99%